Do experimental units of different scale affect the biological performance of European sea bass Dicentrarchus labrax larvae?. Issue 4 (April 2015) - Lika, K.; Pavlidis, M.; Mitrizakis, N.; Samaras, A.; Papandroulakis, N.
<x xml:space="preserve">Abstract</x> The effects of different tank volumes (2000, 500 and 40 l) on European sea bass Dicentrarchus labrax larval rearing, relating to growth, survival, quality and stress variables, were investigated. A dynamic energy budget (DEB) model was used to analyse the results. The hydrodynamics of the tanks exhibited differences, with the water currents in the 2000 l tanks to be almost one order of magnitude stronger than those in the 40 l ones. Important differences in fish growth were observed between small and large tank‐rearing volumes, with the smallest tank resulting in the slowest growth. Based on the DEB model analysis, growth differences were related to feeding rates, with growth in the smaller tank limited by food availability. Differences in survival rates were not statistically significant among the tank‐rearing volumes. The quality evaluation of the fry (in terms of swimbladder, jaw and skeletal abnormalities) showed differences, with the smallest tank having the highest percentage of deformed individuals. This could be attributed to both the feeding variances and the hydrodynamics in the tanks. No differences were observed in terms of whole‐body cortisol at the two developmental stages; flexion, and when the larvae body was fully covered by melanophores; when analysis was performed. This indicates that the allostatic load exerted on fish of different groups was similar and inside the fish‐coping abilities range, in terms of the cortisol response axis. The selection of the experimental scale is of importance, especially when the results are to be transferred and applied on an industrial scale.